RANCANG BANGUN “SMART SUMUR” ALAT PENYEDIAAN SANITASI AIR BERSIH BERBASIS INTERNET OF THINGS DI DAERAH PINGGIRAN SUNGAI CITARUM KABUPATEN BANDUNG - Muhammad Wildan Naufal; Oscar Rachman (POLITEKNIK PIKSI GANESHA, 2023)
This study aims to design a tool that is used as a facility for providing clean water sanitation based on the Internet of Things / (IoT). Clean water is very important for the community, in several densely populated settlements the availability of clean water is starting to be difficult to obtain, especially with the flood disaster that had hit several areas causing indications of water sources mixing with waste which could threaten public health. Based on this, through the use of sensor technology and interconnected devices, polluted water is treated by the system so that it can be regulated and monitored more efficiently. By using sensors that are interconnected to the IoT network, information about water quality, pollution levels, and other important parameters can be seen by the public or the government to monitor water quality. In addition, by using smart sensors connected to the IoT system, water use can be monitored and managed efficiently. The main components used in